Factor Analysis on Measles after The 2017 Measles Rubella Vaccine Campaign in Magetan District - Tutiek Herlina; Triana Septianti Purwanto (Aloha International Journal of Health Advancement (AIJHA), 2019)
Measles is an infectious disease, infecting many children and becomes a major cause of child mortality in Indonesia. This disease is highly contagious, transmitted by viruses through droplets. Undeveloped immunity and low immunization coverage make it potentially epidemic. According to the 2016 Health Profile of Magetan Regency, measles cases were ranked first. Indonesia is committed to achieve the elimination of measles in 2020, with strategies such as the Measles Rubella vaccine campaign for children between 9 months-15 years. The research purpose was to analyze the factor of measles after the 2017 measles rubella vaccine campaign in Magetan Regency. This research used retrospective case control research design, the case sample was all the measles patients after the MR vaccine campaign until July 2018, as many as 16. The control sample was a part of the Magetan Regency population who did not suffer measles, as many as 64, determined with a ratio of 1:4. The research variables were immunization status, gender, exclusive breastfeeding, patient contact history, and knowledge of measles. The results showed that there is an effect of immunization status on the incidence of measles. The probability of someone who was not immunized is 81% for measles infection compared to those who are immunized. There is no influence of gender, exclusive breastfeeding, patient contact history, and knowledge of measles on the incidence of measles. Conclusion: immunization factor is the dominant factor that influence the incidence of measles. Suggestion: to reduce morbidity and mortality rates due to measles, Health Center (Puskesmas) is expected to increase the coverage of measles immunization, supported by highest quality of vaccine and techniques. Keywords: measles, campaign, rubella measles vaccine